Brainstem Auditory Evoked Responses in an Equine Patient Population: Part I – Adult Horses. (5th June 2014) - Aleman, M.; Holliday, T.A.; Nieto, J.E.; Williams, D.C.
<x xml:space="preserve">Abstract</x> Background Brainstem auditory evoked response has been an underused diagnostic modality in horses as evidenced by few reports on the subject. Hypothesis/Objectives To describe BAER findings, common clinical signs, and causes of hearing loss in adult horses. Animals Study group, 76 horses; control group, 8 horses. Methods Retrospective. BAER records from the Clinical Neurophysiology Laboratory were reviewed from the years of 1982 to 2013. Peak latencies, amplitudes, and interpeak intervals were measured when visible. Horses were grouped under disease categories. Descriptive statistics and a posthoc Bonferroni test were performed. Results Fifty‐seven of 76 horses had BAER deficits. There was no breed or sex predisposition, with the exception of American Paint horses diagnosed with congenital sensorineural deafness. Eighty‐six percent (n = 49/57) of the horses were younger than 16 years of age. The most common causes of BAER abnormalities were temporohyoid osteoarthropathy (THO, n = 20/20; abnormalities/total), congenital sensorineural deafness in Paint horses (17/17), multifocal brain disease (13/16), and otitis media/interna (4/4). Auditory loss was bilateral and unilateral in 74% (n = 42/57) and 26% (n = 15/57) of the horses, respectively. The most common causes of bilateral auditory loss were sensorineural deafness, THO, and multifocal brain disease whereas THO and otitis were the most common causes of unilateral deficits. Conclusions and Clinical Importance Auditory deficits should be investigated in horses with altered behavior, THO, multifocal brain disease, otitis, and in horses with certain coat and eye color patterns. BAER testing is an objective and noninvasive diagnostic modality to assess auditory function in horses.